LE FINANCEMENT DES INSTITUTIONS D’ENSEIGNEMENT POST-SECONDAIRE AU QUÉBEC, 1961-2005 / THE FINANCING OF POST-SECONDARY EDUCATION IN QUÉBEC, 1961-2005 - Moussaly-Sergieh, Karim; Vaillancourt, François (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2007)
Ce texte examine l’évolution du financement des institutions d’enseignement post-secondaire et particulièrement des universités au Québec pendant la période 1961-2005, avec des comparaisons avec l’Ontario lorsque faisable et approprié. La première partie dresse un portrait des effectifs étudiants dans les institutions québécoises d’enseignement post-secondaire. La seconde partie présente des indicateurs sur le financement de ces institutions, en termes de niveau et de sources. La troisième partie se penche sur le niveau approprié des frais de scolarité. On y examine le rendement privé associé aux études universitaires, l’impact du niveau de ces frais sur l’accès à l’université et les dimensions redistributives d’un financement public plus ou moins élevé. THE FINANCING OF POST-SECONDARY EDUCATION IN QUÉBEC, 1961-2005 This paper examines the evolution of the financing of post-secondary institutions, particularly universities, in Québec for the 1961-2005 period, with comparisons with Ontario where feasible and appropriate. The first part describes the evolution of enrollment in post-secondary institutions in Québec. The second part presents indicators on the financing of these institutions with respect to their level and sources. The third part addresses the issue of the appropriate level of tuition fees. In it, we examine the returns to university schooling, the impact of these fees on university accessibility and the redistributive impact of a higher or lower level of public funding.